IT outsourcing as an innovative strategy for economic advancement: lessons from Malaysia - Arshad, Y; Ahlan, Abdul Rahman (2013)
IT outsourcing is seen as an innovative strategy for organizations to leverage on its several major benefits. The motivations for ITO can be in forms of technological, economic and business benefits. Moreover, ITO generates income for the nation economy. This is possible in onshore and offshore outsourcing activities. This study explores the literature and our previous studies on ITO in banking and public healthcare sector in Malaysia. We aim to answer the motivations for, risks and challenges in and how ITO contributes towards nations’ economies. The study finds that ITO benefits can be mainly categorized into strategic, economic or business and technological benefits. Risks and challenges faced by the organizations under studies are many which can be grouped into financial, information, technical, human resource, project management, risk management and relationship management. Developing countries can tap on her cost effective and innovative proposals to attract potential clients to outsource their IT services and functions to them.